Synthesis and Characterization Hausmannite (Mn3O4) Nanoparticle of Manganese Ores Prepared By High-Energy Milling - Ratnawulan, Fuji Prasetyo, Ahmad Fauzi, Ramli (International Journal of Advanced Science and Technology, 2020)
In this paper we report synthesis and characterization of hausmanite (Mn3O4) manganese ores nanoparticles from West Sumatera deposit by High- Energy Milling method. The synthesis was carried out using sintering temperature variation of 26 ° C, 600 ° C, 700 ° C, 800 ° C, 900 ° C, and 1000 ° C and milling time of 0 hours, 2 hours, 4 hours, 8 hours and 10 hours. Characterization is done by using X-Ray Fluorescence (XRF) and X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). XRF test results showed that the manganese content was 84.139%. The Hausmanite phase was obtained when the sample was sintered at 7000C. The crystal structure of the Hausmanite phase is tetragonal. We obtained the the hausmanite nanoparticles with homogeneous size distribution could be synthesized at 8 hours of grinding time. The size of the nanoparticles produced is 90.50 nm.